Biaxial Mechanical Properties of Human Ureter under Tension - Rassoli, Aisa; Shafigh, Mohammad; Seddighi, Amirsaeed; Seddighi, Afsoun; Daneshparvar, Hamidreza; Fatouraee, Nasser (Urology Journal, 2014)
Abstract Purpose: The Mechanical properties of the ureteral wall may be altered by certain diseases such as megaureter. Ureter compliance and wall tension alterations can occur, leading to some abnormalities such as reflex mechanisms. Familiarizing with the mechanical properties of the ureter can help us advance in the understanding of urinary tract diseases. Materials and Methods: A constitutive model that can predict the mechanical response of ureteral tissue under complex mechanical loading is required. Parameters characterizing the mechanical behaviour of the material were estimated from planar biaxial test data, where human ureter specimens were simultaneously loaded along the longitudinal and circumferential directions. Results: The biaxial stress-stretch curve was plotted and fitted to a hyperelastic four-parameter Fung type model and five-parameter Mooney-Rivlin model. The average strength in the longitudinal direction was 3.48 ± 0.47 MPa and 2.31 ± 0.46 MPa (P <.05) for the circumferential direction.In the Fung model the value of parameter a2 (0.699 ± 0.17) was higher than a1 (0.279 ± 0.07), which may be due to the collagen fiber orientation’s preference along the longitudinal axis. Conclusion: According to this study, it seems that ureter tissue is stiffer in the longitudinal than in the circumferential direction and maybe the collagen fiber are along the axial axes. Also the specimens showed some degree of anisotropy.